Molecular cloning and expression in Saccharomyces cerevisiae of two Aspergillus nidulans xylanase genes. - Pérez-Gonzalez, J A (1996)
Two Aspergillus nidulans genes, xlnA and xlnB, encoding the X22 and X24 xylanases from this fungus, respectively, have been cloned and sequenced. Their cDNAs have been expressed in a laboratory Saccharomyces cerevisiae strain under the control of a constitutive yeast promoter, resulting in the construction of recombinant xylanolytic yeast strains.